Comparison of outcomes in ST-segment depression and ST-segment elevation myocardial infarction patients treated with emergency PCI: data from a multicentre registry - Knot, Jiri; Kala, Petr; Rokyta, Richard; Stasek, Josef; Kuzmanov, Boyko; Hlinomaz, Ota; Bĕlohlavek, Jan; Rohac, Fili P; Petr, Robert; Bilkova, Dana; Djambazov, Slavejko; Grigorov, Mladen; et al. (Cardiovascular journal of Africa, 2012)
BACKGROUND: Traditionally, acute myocardial infarction (AMI) has been described as either STEMI (ST-elevation myocardial infarction) or non-STEMI myocardial infarction. This classification is historically related to the use of thrombolytic therapy, which is effective in STEMI. The current era of widespread use of coronary angiography (CAG), usually followed by primary percutaneous coronary intervention (PCI) puts this classification system into question. OBJECTIVES: To compare the outcomes of patients with STEMI and ST-depression myocardial infarction (STDMI) who were treated with emergency PCI. METHODS: This multicentre registry enrolled a total of 6 602 consecutive patients with AMI. Patients were divided into the following subgroups: STEMI (n = 3446), STDMI (n = 907), left bundle branch block (LBBB) AMI (n = 241), right bundle branch block (RBBB) AMI (n = 338) and other electrocardiographic (ECG) AMI (n = 1670). Baseline and angiographic characteristics were studied, and revascularisation therapies and in-hospital mortality were analysed. RESULTS: Acute heart failure was present in 29.5% of the STDMI vs 27.4% of the STEMI patients (p < 0.001). STDMI patients had more extensive coronary atherosclerosis than patients with STEMI (three-vessel disease: 53.1 vs 30%, p < 0.001). The left main coronary artery was an infract-related artery (IRA) in 6.0% of STDMI vs 1.1% of STEMI patients (p < 0.001). TIMI flow 0-1 was found in 35.0% of STDMI vs 66.0% of STEMI patients (p < 0.001). Primary PCI was performed in 88.1% of STEMI (with a success rate of 90.8%) vs 61.8% of STDMI patients (with a success rate of 94.5%) (p = 0.012 for PCI success rates). In-hospital mortality was not significantly different (STDMI 6.3 vs STEMI 5.4%, p = 0.330). CONCLUSION: These data suggest that similar strategies (emergency CAG with PCI whenever feasible) should be applied to both these types of AMI.
Keywords: urgentní zdravotnické služby; Registries; Humans; lidé středního věku; analýza přežití; koronární angioplastika; Electrocardiography; registrace; koronární cévy; Coronary Vessels; Female; Aged; výsledek terapie; senioři; lidé; infarkt myokardu; Survival Analysis; Follow-Up Studies; ženské pohlaví; Male; Middle Aged; Myocardial Infarction; Treatment Outcome; Aged, 80 and over; Percutaneous Coronary Intervention; senioři nad 80 let; mužské pohlaví; následné studie; Emergency Medical Services; elektrokardiografie